glass

KR103012592B1Active Publication Date: 2026-09-02AGC INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
KR1020227043128
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-25
Filing Date
2021-06-02
Publication Date
2026-09-02
Estimated Expiration
2041-06-02

Smart Images

  • Figure 112022132014313-PCT00001
    Figure 112022132014313-PCT00001
  • Figure 112022132014313-PCT00002
    Figure 112022132014313-PCT00002
  • Figure 112022132014313-PCT00003
    Figure 112022132014313-PCT00003
Patent Text Reader

Abstract

The present invention relates to a glass containing, in molar percentages based on oxides, SiO2; 52 to 80%, B2O3; 5 to 30%, Al2O3; 2 to 30%, P2O5; 0.1 to 11%, and Na2O; 0.0001 to 5%, and having an average coefficient of thermal expansion α of 5×10-7 / ℃ or more and less than 33×10-7 / ℃.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to glass suitable for the top plate of a heater. Background Technology

[0002] In heating devices such as heating cookers, the top plate on which the object to be heated, such as a pot, is placed requires heat resistance. For this reason, crystallized glass plates with an extremely small coefficient of thermal expansion are used.

[0003] For example, in Patent Document 1, the average coefficient of thermal expansion in the range of 30 to 750°C is -5×10 -7 Up to 30×10 -7 A glass composition of / ℃ is disclosed.

[0004] In addition, Patent Document 2 describes an average coefficient of thermal expansion of 15×10 in the range of 50 to 350℃. -7 Up to 30×10 -7 A glass composition of / ℃ is disclosed. Prior art literature

[0005] Japanese Patent Publication No. Hei 11-100229 Japanese Patent Publication No. 2018-203571 The problem to be solved

[0006] However, generally, crystallized glass plates contain two phases: a crystalline phase and a glass phase. Because of this, although they have heat resistance, there are manufacturing difficulties that require uniform heat treatment, and there was a problem that the plate thickness could not be increased.

[0007] Common glass plates include TEMPAX (a registered trademark of SCHOTT), which contains B2O3 to provide heat resistance. However, the average coefficient of thermal expansion is 33×10⁻⁶ -7 Since it was approximately / ℃, it was the upper limit for the average coefficient of thermal expansion that can be produced in a conventional melting furnace.

[0008] Therefore, in order to lower the average coefficient of thermal expansion, it is considered to increase the B2O3 content or add Al2O3. However, if the B2O3 content is increased, the viscosity of the molten glass increases, making it impossible to manufacture in a conventional melting furnace. In addition, if Al2O3 is added, depending on the amount added, devitrification or powdering is likely to occur during manufacturing.

[0009] To resolve these issues, adding Na2O to the glass components is effective; however, there was a challenge in that the inclusion of Na2O increased the average coefficient of thermal expansion, resulting in high expansion. Although there is a demand for heat-resistant materials with thick plates, no glass plate has been discovered to date that achieves a balance of low expansion, devitrification suppression, and phase dispersion suppression.

[0010] In addition, when used as a top plate for placing objects to be heated, such as pots, there was a problem where it broke during heating due to scratches caused by contact with the pot.

[0011] The present invention aims to provide a low-expansion rate glass having low expansion and excellent heat resistance, as well as excellent inhibition of devitrification and pulverization, and a heat-resistant member using said glass. means of solving the problem

[0012] <1>

[0013] In the molar percentage representation based on oxides,

[0014] SiO2; 52 to 80%,

[0015] B2O3; 5 to 30%,

[0016] Al2O3; 2 to 30%,

[0017] P2O5; 0.1 to 11%,

[0018] Na2O; 0.0001 to 5%

[0019] Contains, and the average coefficient of thermal expansion α at 50 to 350°C is 5×10-7 / ℃ or higher 33×10 -7 Glass below / ℃.

[0020] <2>

[0021] Linear transmittance T at a wavelength of 850 nm for a glass plate thickness of 15 mm 850 The above which is 87.5% or more <1> Glass listed in

[0022] <3>

[0023] Additionally, in the molar percentage expression based on oxides,

[0024] Fe2O3; 0.00001 to 0.03%

[0025] The above containing <1> or <2> Glass listed in

[0026] <4>

[0027] The above glass, expressed as a molar percentage based on oxide,

[0028] SiO2+Al2O3; 76.5 to 85%,

[0029] R2O: 0.01 to 5%

[0030] (wherein R2O is at least one of Li2O or K2O)

[0031] The above containing <1> inside <3> Glass listed in any one of them.

[0032] <5>

[0033] Additionally, in the molar percentage expression based on oxides,

[0034] MgO; 0.1 to 10%

[0035] The above containing <1> inside <4> Glass listed in any one of them.

[0036] <6>

[0037] Additionally, in the molar percentage expression based on oxides,

[0038] CaO; 0.1 to 3%

[0039] The above containing <1> inside <5> Glass listed in any one of them.

[0040] <7>

[0041] The above glass, expressed as a molar percentage based on oxide,

[0042] SiO2; 55 to 68%,

[0043] Al2O3; 8.5 to 30%

[0044] and also, the ratio of P2O5 and Al2O3

[0045] P2O5 / Al2O3; 0.1 to 1.0

[0046] In the above <1> inside <6> Glass listed in any one of them.

[0047] <8>

[0048] The above glass, expressed as a molar percentage based on oxide,

[0049] SiO2+Al2O3+B2O3+P2O5; 89 to 99%

[0050] And also, the sum of Al2O3 and B2O3 and the ratio of SiO2+P2O5

[0051] (Al2O3+B2O3) / (SiO2+P2O5)≥0.3

[0052] In the above <1> inside <7> Glass listed in any one of them.

[0053] <9>

[0054] The above glass, expressed as a molar percentage based on oxide,

[0055] (CaO+Na2O+P2O5) / Al2O3≥0.35

[0056] In the above <6> inside <8> Glass listed in any one of them.

[0057] <10>

[0058] The above <1> inside <9> A glass plate containing glass described in any one of the following.

[0059] <11>

[0060] The above glass plate having a plate thickness of 4 to 150 mm <10> Glass plate listed in

[0061] <12>

[0062] The above <10> or <11> A heat-resistant member formed by bonding ceramics having a thermal conductivity of 25 Wm / K or higher to a glass plate described in [the text].

[0063] <13>

[0064] The above <10> or <11> For ceramics having a thermal conductivity of 25 Wm / K or higher on the glass plate described herein, the difference in the coefficient of expansion in the range of 50 to 200°C is ±6.0 × 10 -7 A heat-resistant member formed by bonding ceramics within the range of / ℃.

[0065] <14>

[0066] The ceramics above are bonded by fluoropolymer bonding, <12> or <13> Heat-resistant member as described in Effects of the invention

[0067] According to one embodiment of the present invention, a low expansion rate glass having low expansion and excellent heat resistance, as well as excellent inhibition of devitrification and pulverization, and a heat-resistant member using said glass can be provided. Specific details for implementing the invention

[0068] Hereinafter, a glass of one embodiment of the present invention will be described in detail.

[0069] However, the present invention is not limited to the following embodiments, and may be implemented with arbitrary modifications within the scope that does not deviate from the gist of the present invention.

[0070] [Explanation of Terms]

[0071] In this specification, the following applies.

[0072] "To" means that it is greater than or equal to the lower limit value and less than or equal to the upper limit value.

[0073] The composition of the glass is expressed as a molar percentage based on oxides, and the content of components with fluctuating valence in the glass is expressed by converting them into representative oxides.

[0074] Unless otherwise noted, "%" refers to the molar percentage based on oxides.

[0075] "Substantially not containing" in relation to the glass composition means not containing, except for unavoidable impurities.

[0076] The glass of one embodiment of the present invention refers to an amorphous glass in which diffraction peaks indicating crystals are not observed by X-ray diffraction, and does not include crystallized glass.

[0077] [glass]

[0078] A glass of one embodiment of the present invention contains, in molar percentage based on oxides, SiO2; 52 to 80%, B2O3; 5 to 30%, Al2O3; 2 to 30%, P2O5; 0.1 to 11%, and Na2O; 0.0001 to 5%, and has an average coefficient of thermal expansion α of 5×10⁻⁶ at 50 to 350°C. -7 / ℃ or higher 33×10 -7 It is less than / ℃.

[0079] SiO2 is an essential and main component for forming the mesh of the glass. SiO2 is contained in an amount of 52% or more to increase the heat resistance of the glass and to make it less susceptible to scratches from mechanical impact. The SiO2 content is preferably 55% or more, more preferably 60% or more, and even more preferably 65% ​​or more.

[0080] SiO2 is contained in an amount of 80% or less to lower viscosity during glass manufacturing. The SiO2 content is preferably 78% or less, more preferably 75% or less, even more preferably 70% or less, and particularly preferably 68% or less.

[0081] The range of SiO2 content can be specified by any combination of their upper and lower limits.

[0082] B2O 3은 It is an essential component for promoting the melting of glass raw materials while maintaining low expansion. B2O3 is contained in an amount of 5% or more to improve mechanical properties or weather resistance and to achieve low expansion. The content of B2O3 is preferably 8% or more, more preferably 10% or more, even more preferably 12% or more, and particularly preferably 13% or more.

[0083] B2O3 is contained in an amount of 30% or less to prevent problems such as the formation of ream due to volatilization, erosion of the furnace wall, and reduced water resistance. The content of B2O3 is preferably 25% or less, more preferably 20% or less, and even more preferably 15% or less.

[0084] The range of B2O3 content can be specified by any combination of their upper and lower limits.

[0085] Al2O 3은 It is an essential component for forming a mesh of glass and modifying the mesh of glass. Al2O3 is contained in an amount of 2% or more to increase the heat resistance of the glass and to prevent weathering or dust formation. The content of Al2O3 is preferably 5% or more, more preferably 8.5% or more, even more preferably 10% or more, and even more preferably 13% or more.

[0086] Al2O3 is contained in an amount of 30% or less to lower viscosity during glass manufacturing and to suppress devitrification. The content of Al2O3 is preferably 25% or less, more preferably 20% or less, and even more preferably 15% or less. The range of Al2O3 content can be specified by any combination of the upper and lower limits thereof.

[0087] P2O5 is an essential component for preventing crystallization or devitrification of the glass. P2O5 is contained in an amount of 0.1% or more to stabilize the glass. The content of P2O5 is more preferably 2% or more, more preferably 3% or more, and particularly preferably 3.5% or more.

[0088] P2O5 is contained in an amount of 11% or less because it can stabilize the glass without making the high-temperature viscosity of the glass too high. The content of P2O5 is preferably 9.5% or less, more preferably 9% or less, even more preferably 8% or less, and particularly preferably 5% or less.

[0089] The range of P2O5 content can be specified by any combination of their upper and lower limits.

[0090] Na2O is an essential component for improving the electrical conductivity of glass at high temperatures, promoting the melting of glass raw materials, and adjusting the coefficient of thermal expansion and viscosity of the glass. Na2O is contained in an amount of 0.0001% or more to improve the solubility, clarity, and moldability of the glass at high temperatures. The content of Na2O is preferably 0.0005% or more, more preferably 0.01% or more, and even more preferably 0.5% or more.

[0091] Na2O is contained in an amount of 5% or less to reduce the coefficient of thermal expansion of the glass and to reduce stress generated during temperature changes in order to suppress cracks caused by thermal shock. From the perspective of achieving a desired average coefficient of thermal expansion, the content of Na2O is preferably 3% or less, more preferably 2.5% or less, and even more preferably 1% or less.

[0092] The range of Na2O content can be specified by any combination of their upper and lower limits.

[0093] The average thermal expansion coefficient α of the glass in one embodiment of the present invention is 5×10⁻⁶ in a temperature range of 50 to 350°C. -7 / ℃ or higher 33×10-7 It is less than / ℃. The average coefficient of thermal expansion α is 7×10⁻⁶ in terms of bonding with ceramics. -7 / ℃ or higher is desirable, and 10×10 -7 / ℃ or higher is more desirable, and 15×10 -7 / ℃ or higher is more desirable, and 20×10 -7 Above / ℃ is particularly desirable.

[0094] The average coefficient of thermal expansion α is 30×10⁻⁶ to suppress cracking caused by thermal shock by minimizing thermal stress generated during temperature changes. -7 / ℃ or lower is desirable, and 28×10 -7 / ℃ or lower is more desirable, and 27×10 -7 It is more desirable to have a temperature of / ℃ or lower.

[0095] A glass of one embodiment of the present invention, having a glass plate thickness of 15 mm, has a linear transmittance T at a wavelength of 850 nm. 850 By making it 87.5% or higher, infrared rays can be efficiently transmitted. Therefore, in the case of a laminate in which SiC is laminated onto glass according to one embodiment of the present invention, the SiC can be efficiently heated by infrared rays from a heater irradiated onto the glass side. From the perspective of efficiency during heater heating, the linear transmittance T 850 88% or more is more desirable, 89% or more is even more desirable, and 90% or more is even more desirable.

[0096] Linear transmittance T 850 For example, it can be measured using a double-beam spectrophotometer (model V-650 manufactured by Nihon Bunko Co., Ltd.), measured in a measurement wavelength range of 400 to 1200 nm, and the transmittance at a measurement wavelength of 850 nm is taken as the linear transmittance.

[0097] In one embodiment of the present invention, the glass preferably additionally contains 0.00001 to 0.03% of Fe2O3, expressed as a molar percentage based on oxides. In order to control the temperature of the bottom substrate of the melting furnace by improving the clarity of the glass while maintaining linear transmittance at a wavelength of 850 nm without damaging the color of the glass, the content of Fe2O3 is more preferably 0.0001% or more, and even more preferably 0.0005% or more.

[0098] To maintain the color of the glass, Fe2O 3은 0.02% or less is more preferable, and 0.01% or less is even more preferable. The range of Fe2O3 content can be specified by any combination of the upper and lower limits thereof.

[0099] A glass of one embodiment of the present invention preferably contains SiO2+Al2O3; 76.5 to 85%, and R2O: 0.01 to 5% (provided that R2O is at least one of Li2O or K2O).

[0100] By making the SiO2+Al2O3 content 76.5 to 85%, the glass can be made low-expansion. The total content of SiO2 and Al2O3 is more preferably 77% or more, and even more preferably 78% or more.

[0101] In order to enable manufacturing by lowering the devitrification temperature, the total amount of SiO2 and Al2O3 is more preferably 83% or less, even more preferably 82% or less, and even more preferably 80% or less.

[0102] R2O is a useful component for improving the electrical conductivity of glass at high temperatures. It is also a useful component for promoting the melting of glass raw materials and for adjusting the coefficient of thermal expansion, viscosity, etc., of the glass. Here, R2O represents at least one of Li2O or K2O.

[0103] The R2O content is preferably 0.01% or more, more preferably 0.1% or more, and even more preferably 0.5% or more. By reducing the coefficient of thermal expansion of the glass, the stress generated during temperature changes can be reduced.

[0104] The content of R2O is preferably 5.0% or less, more preferably 4.0% or less, even more preferably 3.0% or less, and even more preferably 1% or less.

[0105] The range of R2O content can be specified by any combination of their upper and lower limits.

[0106] The glass of one embodiment of the present invention preferably further contains 0.1 to 10% of MgO, expressed as a molar percentage based on oxides. In order to increase manufacturability by lowering the viscosity of the glass while maintaining low expansion, the amount of MgO is preferably 0.1% or more, more preferably 0.5% or more, even more preferably 1% or more, and even more preferably 2% or more.

[0107] In order to increase productivity by lowering the devitrification temperature of the glass while having low expansion, MgO is preferably 10% or less, more preferably 8% or less, and more preferably 6% or less.

[0108] The range of MgO content can be specified by any combination of these upper and lower limits.

[0109] The glass of one embodiment of the present invention additionally preferably contains 0.1 to 3% of CaO, expressed as a molar percentage based on oxides. In order to increase manufacturability by lowering the viscosity of the glass while maintaining low expansion, the CaO content is preferably 0.1% or more, more preferably 0.3% or more, and even more preferably 0.5% or more.

[0110] In addition, to increase productivity by lowering the devitrification temperature of the glass while maintaining low expansion, it is preferable that the CaO content be 3% or less, more preferable that it be 2% or less, and more preferable that it be 1% or less.

[0111] The range of CaO content can be specified by any combination of these upper and lower limits.

[0112] In one embodiment of the present invention, the glass is further preferably composed of SiO2; 55 to 68% and Al2O3; 8.5 to 30% in molar percentage based on oxides, and the ratio of the content of P2O5 to Al2O3, P2O5 / Al2O3, is preferably 0.1 to 1.0.

[0113] If P2O5 / Al2O3 is less than 0.1, the glass becomes unstable, making vitrification difficult, or the crystallization temperature is lowered. If it exceeds 1.0, there is a concern that chemical resistance may decrease, or the viscosity of the glass may become too high. P2O5 / Al2O3 is more preferably 0.3 to 0.8, even more preferably 0.35 to 0.7, and most preferably 0.40 to 0.65.

[0114] A glass of one embodiment of the present invention additionally comprises 89 to 99% SiO2+Al2O3+B2O3+P2O5 in molar percentage based on oxides, and it is preferable that (Al2O3+B2O3) / (SiO2+P2O5), which is the ratio of the sum of Al2O3 and B2O3 to SiO2+P2O5, is 0.3 or higher. That is, it is preferable that (Al2O3+B2O3) / (SiO2+P2O5) ≥ 0.3. If (Al2O3 and B2O3) / (SiO2+P2O5) is less than 0.3, the glass becomes unstable and prone to pulverization, or the devitrification temperature is lowered, and furthermore, the viscosity of the glass becomes too high.

[0115] (Al2O3 and B2O3) / (SiO2+P2O5) is preferably 0.33 or higher, more preferably 0.35 or higher.

[0116] In addition, the glass of one embodiment of the present invention preferably has (CaO+Na2O+P2O5) / Al2O3 ≥ 0.35, expressed as a molar percentage based on oxides. If (CaO+Na2O+P2O5) / Al2O3 is less than 0.35, the glass devitrification temperature increases, and there is a risk that manufacturing characteristics will deteriorate.

[0117] (CaO+Na2O+P2O5) / Al2O 3은 Preferably 0.4 or higher, more preferably 0.45 or higher.

[0118] If necessary, the glass of one embodiment of the present invention may contain RO (wherein RO is at least one of SrO, BaO, and ZnO) to lower the viscosity of the glass, increase solubility, and control the expansion coefficient. The content of RO is preferably 0.1% or more, more preferably 1.5% or more, and even more preferably 3.0% or more.

[0119] In order to lower the devitrification temperature of the glass to increase solubility and control the expansion coefficient, RO is preferably 12% or less, more preferably 10% or less, even more preferably 7.5% or less, and even more preferably 5% or less.

[0120] The glass composition of one embodiment of the present invention is not limited to this in order to achieve the purpose, and, for example, TiO2, ZrO2, and Y2O3 may be appropriately added in a range of 0 to 5% each.

[0121] The method of manufacturing glass according to one embodiment of the present invention is not particularly limited, and the method of molding molten glass is also not particularly limited, but it can be manufactured as, for example, as follows.

[0122] First, glass raw materials are prepared appropriately, heated to about 1600 to 1700°C and melted, then homogenized by degassing, stirring, etc., and formed into a plate or block by casting using the well-known float method, downdraw method (fusion method, etc.), press method, roll-out method, slip cast method, etc., and then cut to a desired size after slow cooling to produce glass (glass plate).

[0123] Grinding is performed as necessary, but it is also possible to treat the surface of the glass plate with a fluorine agent in addition to or instead of grinding. Considering the stable production of glass plates, the float method or the downdraw method is preferable, and the float method is particularly preferable when considering the production of large glass plates.

[0124] In addition, when using this glass, physical strengthening may be performed to improve scratch resistance or heat resistance.

[0125] [Glass plate]

[0126] A glass plate of one embodiment of the present invention comprises the glass. That is, it is a glass plate formed by molding the glass by a desired manufacturing method.

[0127] Although the thickness of the glass plate is not particularly limited, from the perspective of supporting heavy objects as a top plate on which a heating cooker or the like is placed, or from the perspective of infrared transmittance as a heat-resistant member described later, 4 to 150 mm is preferred, 5 to 120 mm is more preferred, 7 to 100 mm is even more preferred, and 10 to 30 mm is even more preferred.

[0128] The shape of the glass plate can be appropriately desired, and for example, it can be rectangular or approximately circular.

[0129] [Heat-resistant component]

[0130] Although the use of the glass and glass plate of one embodiment of the present invention is not particularly limited, since it is a low-expansion glass with excellent heat resistance and excellent suppression of devitrification and dusting, it can be suitably used in various applications such as top plates for heaters like heating cookers, window materials for high-temperature furnaces, and building materials requiring fire resistance.

[0131] Among these, the top plate of a heating device, such as a heating cooker, can be particularly suitable for use. As for the heating cooker, in addition to an induction heating type heating cooker (induction heating cooker), it may be a gas combustion type heating cooker (gas heating cooker), or a kitchen glass die containing said heating cooker.

[0132] In addition, since the glass of one embodiment of the present invention is a transparent glass rather than a crystallized glass, a coloring component may be appropriately added depending on the surrounding color tone or design.

[0133] For example, when considering application to the top plate of a heating cooker, an organic printing layer containing an inorganic filler, such as ink, may be further provided on the surface thereof to conceal the interior of the heating cooker. Typically, this organic printing layer containing an inorganic filler is provided on the surface opposite to the surface contacted by the object to be heated on the top plate of the heating cooker (the reverse side). Furthermore, although the color tone of the organic printing layer containing an inorganic filler is not particularly limited, it is preferable to match the color tone with that of the kitchen die placed around the heating cooker so that a sense of color tone unity can be provided.

[0134] In one embodiment of the present invention, the thermal conductivity of the ceramic attached to the upper surface of the glass plate is preferably 25 Wm / K or higher. If it is less than 25 Wm / K, it becomes difficult to raise the temperature at a high speed. Preferably, it is 35 Wm / K or higher, more preferably 50 Wm / K or higher, even more preferably 100 Wm / K or higher, and even more preferably 150 Wm / K or higher.

[0135] In addition, this ceramic material has a difference in coefficient of expansion with glass in the range of 50 to 200°C of ±6.0 × 10⁻⁶. -7 Within the range of / ℃ (-6.0×10⁻⁶ -7 / ℃ or higher 6.0×10 -7 It is desirable that it be (below / ℃). ±6.0×10 -7 If the temperature deviates from the / ℃ range, stress is generated due to the difference in expansion coefficients between ceramics and glass, and there is a risk of warping or breakage during rapid heating or cooling.

[0136] The above difference in expansion coefficient is preferably ±5×10 -7 Within the range of / ℃ (-5×10 -7 / ℃ or higher 5×10 -7 / ℃ or less), and more preferably ±3×10 -7 Within the range of / ℃ (-3×10 -7 / ℃ or higher 3×10 -7 / ℃ or less), and more preferably, ±1.5×10 -7 Within the range of / ℃ (-1.5×10 -7 / ℃ or higher 1.5×10 -7 / ℃ or less), particularly preferably ±1×10 -7 Within the range of / ℃ (-1×10 -7 / ℃ or higher 1×10 -7 / ℃ or less)

[0137] The average coefficient of thermal expansion α of glass at 50 to 350°C is 5×10 -7 / ℃ or higher 33×10 -7 Considering that it is less than / ℃, it is preferable that the ceramic material be at least one of SiC, Si-SiC and Si3N4.

[0138] In Si-SiC, it is preferable that the Si content be 5 to 55 wt%. If it is less than 5 wt%, the expansion increases, making it difficult to obtain sufficient thermal shock properties. On the other hand, if it exceeds 55 wt%, the Young's modulus decreases, and the bending strength decreases. The Si content is preferably 14 to 40 wt%, more preferably 17 to 35 wt%, and particularly preferably 20 to 30 wt%.

[0139] In addition, for bonding this ceramic material and glass, it is preferable to use a fluoropolymer resin in terms of heat resistance and acid resistance. Examples of fluoropolymer resins include PTFE (polytetrafluoroethylene) and PFA (tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer).

[0140] It is preferable to bond a ceramic having a thermal conductivity of 25 Wm / K or higher to a glass plate of one embodiment of the present invention by the fluoropolymer bonding.

[0141] In addition, the adhesive strength is preferably 25 MPa or higher in tensile strength.

[0142] In addition, to ensure heat resistance, the glass transition point is preferably 150°C or higher, more preferably 200°C or higher, and even more preferably 250°C or higher.

[0143] In addition, Young's modulus is preferably 2.5 GPa or less.

[0144] As described above, by bonding the glass plate and ceramics using a fluoropolymer, it is suitable because it is possible to prevent damage caused by scratching of the top plate.

[0145] Examples

[0146] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited thereto.

[0147] Examples 1 to 27 are examples, and Examples 28 to 30 are comparative examples.

[0148] [pharmacy]

[0149] Raw materials were prepared to have the compositions listed in Tables 1 and 2, expressed as molar percentages based on oxides, placed in a platinum crucible, and introduced into a resistance-heated electric furnace at 1650°C to melt for 3 hours, degass, and homogenize. Additionally, blank spaces in Tables 1 and 2 indicate that the corresponding component is not contained.

[0150] The obtained glass melt was poured into a mold and maintained at a temperature of glass transition temperature Tg + 50°C for 3 hours, then cooled to room temperature at a rate of 1°C / min to obtain glass blocks of Examples 1 to 30. In addition, the obtained glass blocks were cut into glass plates to obtain glass plates.

[0151] [Average coefficient of thermal expansion α]

[0152] A round bar measuring φ4.0mm × length 20mm was cut from the obtained glass plate, and based on JIS R 3102, the average coefficient of thermal expansion α at 50 to 350℃ (unit: ℃) -1 ) was measured using a thermomechanical analyzer (BRUKER TDS5000SA). The results are shown in Tables 3 and 4.

[0153] [Evaluation of Real Investment]

[0154] For the obtained glass block, the temperature serving as the standard for glass devitrification, that is, the viscosity of the glass, is 10 3 The temperature T3 at which dPa·s was obtained was measured using a rotational viscometer. The temperature was maintained at T3 for 15 hours, and the presence or absence of devitrification was observed visually. The presence of crystals was marked ×, and the absence was marked ○. The results are shown in Tables 3 and 4.

[0155] [Evaluation of the Division]

[0156] A round bar measuring φ4.0 mm × length 20 mm was cut from the obtained glass block and measured using a thermomechanical analyzer (BRUKER TDS5000SA). Samples that showed a curve near Tg, were unmeasurable, or appeared cloudy to the naked eye were considered to be pulverized and marked ×, while others were marked ○. The results are shown in Tables 3 and 4. In cases of pulverization, an accurate coefficient of thermal expansion curve cannot be obtained.

[0157] [Linear Transmittance]

[0158] The obtained glass block was cut and polished, and processed to a thickness of 15 mm so that both sides were mirror-polished to obtain a glass plate. Linear transmittance was measured using a double-beam spectrophotometer (Type V-650 manufactured by Nihon Bunko Co., Ltd.). Measurements were taken in the measurement wavelength range of 400 to 1200 nm, and the transmittance at a measurement wavelength of 850 nm was defined as the linear transmittance. The results are shown in Tables 3 and 4.

[0159] [Thermal Shock Test]

[0160] The obtained glass plates (Examples 1 to 30) were polished so that both sides became mirror-like, and the size of these glass plates was processed to 100mm × 100mm × 4mm, or the size of the composite members (Examples 1, 10, TEMPAX) produced below was processed to 100mm × 100mm × 22mm. These were heated at 250°C for 10 minutes and dropped into water three times; × was used to indicate that all were broken, and ○ was used to indicate that none were broken. Tables 3 and 4 show the evaluation results of the glass plates, and Table 5 shows the evaluation results of the composite members. For the evaluation results in Tables 3 and 4, a glass plate with a size of 100mm × 100mm × 4mm was used, and for the evaluation results in Table 5, a glass plate with a size of 100mm × 100mm × 22mm was used.

[0161] In addition, the above composite member was manufactured as follows.

[0162] First, the above-mentioned glass blocks (Examples 1 and 10) and TEMPAX (a registered trademark of Corning Inc.) were cut and polished, and processed to a thickness of 15 mm so that both sides were mirror-surfaced to obtain a glass plate.

[0163] Next, the Si-SiC member and SiC member obtained as described below were processed to a thickness of 7 mm so that both sides were mirror-surfaced, and a ceramic plate was obtained.

[0164] <Si-SiC 부재>

[0165] 71.0 wt% of SiC powder (manufactured by Taiheiyo Random Co., Ltd., model number: GMF-12S (average particle size 0.7 μm)), 2.0 wt% of carbon black (average particle size 0.03 μm), 5.5 wt% of metholoose (manufactured by Shinetsu Chemical Co., Ltd., model number: SM8000) as a binder, and 21.5 wt% of pure water were fed into a mixing machine (manufactured by Miyazaki Tekko Co., Ltd., model number: MP100) and mixed for 6 hours to obtain a clay mixture. The obtained clay mixture was fed into an extrusion molding machine (manufactured by Miyazaki Tekko Co., Ltd., model number: FM100) and extruded under conditions of a head pressure of 1.0 MPa and a discharge rate of 1200 g / min to obtain a molded body. The obtained molded body was dried at 50°C for 4 days, then heated in an atmospheric temperature of 450°C for 3 hours and degreased to obtain a degreased body. The obtained degreased body was placed in a carbon kiln 10 -3 A sintered body was obtained by firing at 1700°C for 2 hours under a vacuum atmosphere of Pa. After firing, Si was impregnated under an argon atmosphere at 1670°C to obtain a Si-SiC component.

[0166] <SiC 부재>

[0167] 93.6 wt% of SiC powder (manufactured by Taiheiyo Random Co., Ltd., model number: GMF-12S (average particle size 0.7 μm)), 1.9 wt% of B4C powder (manufactured by Kojundo Kagaku Genkyusho Co., Ltd., model number: BBI10PB (average particle size 0.5 μm)) as a sintering aid, 1.5 wt% of carbon powder (manufactured by Showa Denko Co., Ltd., model number: UF-G5 (average particle size 3 μm)), 3.0 wt% of polyoxyethylene lauryl ether as a dispersant, anhydrous ethanol as a medium, and high-purity silicon carbide balls with a diameter of 5 mm as a grinding medium were added to a nylon ball mill pot, and mixed and ground using a rotary ball mill for 96 hours. The obtained slurry was dried under reduced pressure to obtain raw material powder. The obtained raw material powder was weighed to obtain a sintered body of the desired thickness, pressed using a cold isostatic press at a pressure of 2000 kg / ㎠, and a molded body was obtained. The obtained molded body was placed in a carbon container and fired in a carbon kiln for 10 -3 A SiC sintered body was obtained by sintering at 2150°C for 1 hour under a vacuum atmosphere of Pa.

[0168] Next, a 50 μm PFA film was placed on the 7 mm thick ceramic member (Si-SiC member or SiC member) obtained above, and a 15 mm thick glass plate obtained above was laminated on the film together with the bonding resin described in Table 5, and heat pressing was performed at 300°C for 30 minutes at 1 MPa, which is greater than the Tg of the film, and cooled to room temperature while under pressure to obtain a composite member of ceramics and glass plate (Examples 1, 10, TEMPAX).

[0169]

[0170]

[0171]

[0172]

[0173]

[0174] Examples 1 to 27 were low-expansion glass that had low expansion and excellent heat resistance, as well as excellent devitrification and pulverization inhibition, and also had excellent transmittance at 850 nm and thermal shock resistance. In addition, regarding thermal shock resistance when bonded with ceramics, the composite members of the examples (Examples 1 and 10) were superior compared to the case where TEMPAX of the comparative example was used.

[0175] Meanwhile, comparative examples 28 to 30 did not achieve low expansion, heat resistance, devitrification suppression, and phase suppression, and thermal shock was also poor. In addition, since Example 29 was phase-dispersed, an accurate coefficient of thermal expansion curve could not be obtained.

[0176] Although various embodiments have been described above, it goes without saying that the present invention is not limited to these examples. It is clear to those skilled in the art that various modifications or variations can be made within the scope described in the claims, and that such variations are naturally understood to fall within the technical scope of the present invention. Furthermore, the components of the above embodiments may be combined arbitrarily within the scope that does not deviate from the spirit of the invention.

[0177] In addition, this application is based on the Japanese patent application filed on June 10, 2020 (Japanese patent application No. 2020-101051) and the Japanese patent application filed on September 25, 2020 (Japanese patent application No. 2020-161312), the contents of which are incorporated by reference during this application.

Claims

Claim 1 Expressed as molar percentages based on oxides, it contains SiO2; 52 to 80%, B2O3; 5 to 30%, Al2O3; 2 to 30%, P2O5; 0.1 to 11%, Na2O; 1.2 to 3.2%, CaO; 0.1 to 3%, and Fe2O3; 0.00001 to 0.03%, (CaO+Na2O+P2O5) / Al2O3≥0.45, and the average coefficient of thermal expansion α at 50 to 350°C is 5×10⁻⁶ -7 / ℃ or higher 33×10 -7 Linear transmittance T at a wavelength of 850 nm for a glass plate thickness of 15 mm and less than / ℃ 850 This glass is over 90%. Claim 2 delete Claim 3 delete Claim 4 The glass of claim 1, wherein the glass contains, in molar percentage based on oxides, SiO2+Al2O3; 76.5 to 85%, B2O3; 5 to 20%, and R2O: 0.01 to 5% (provided that R2O is at least one of Li2O or K2O). Claim 5 In claim 1, additionally, glass containing 0.1 to 10% MgO in molar percentage based on oxides. Claim 6 delete Claim 7 The glass according to claim 1, wherein the glass is expressed in molar percentages based on oxides as follows: SiO2; 55 to 68%, Al2O3; 8.5 to 30%, and also the ratio of P2O5 to Al2O3 is P2O5 / Al2O3; 0.1 to 1.

0. Claim 8 The glass according to claim 1, wherein the glass is 89 to 95.8% SiO2+Al2O3+B2O3+P2O5 in molar percentage based on oxides, and furthermore, the ratio of the sum of Al2O3 and B2O3 to SiO2+P2O5 is (Al2O3+B2O3) / (SiO2+P2O5)≥0.

3. Claim 9 delete Claim 10 A glass plate comprising the glass described in paragraph 1. Claim 11 In item 10, a glass plate having a plate thickness of 4 to 150 mm. Claim 12 A heat-resistant member formed by bonding ceramics having a thermal conductivity of 25 Wm / K or higher to a glass plate described in claim 10. Claim 13 For ceramics having a thermal conductivity of 25 Wm / K or higher in the glass plate described in claim 10, the difference in the coefficient of expansion in the range of 50 to 200°C is ±6.0 × 10 -7 A heat-resistant member formed by bonding ceramics within the range of / ℃. Claim 14 In claim 12, a heat-resistant member formed by bonding the ceramics by fluoropolymer bonding. Claim 15 delete Claim 16 In claim 1, the average coefficient of thermal expansion α at 50 to 350°C is 24×10 -7 / ℃ or higher 33×10 -7 Glass below / ℃.

Citation Information

Patent Citations

  • Glass and glass ceramic each with high specific modulus and their use

    JP2000327365A

  • Support-platform-integrated type dielectrics resonator and its fabricating method

    JP2005086711A

  • Glass for anodic bonding

    JP2012020894A

  • Support device

    JP2014165459A

  • Wafer chuck and method of forming wafer chuck

    JP2008199006A